Philippine medical thesaurus on anatomy animal structures, body regions, stomatognathic system and urogenital system in Cebuano - Nicolas, Marisol DC (2004)
Language is a very powerful tool in communicating one's ideas, feelings, and emotions. There is no such thing as a superior language than the other. All languages have about the same level of structural complexity overall and are capable of allowing their speakers to describe the world in which they live in (SIL International, 2004).Realizing this, the need for tools representative of Philippine languages would be relevant. The field of medicine has long been addressing the problem in information management. With its rapid progression due to continuing researches and innovations, information in this field are rapidly expanding and getting more complicated.